Ecological Diversity Of Aquatic Insects With Emphasis On Mosquito Of Qatar And Perception As Well As Awareness Level Among Qatari Toward Mosquito-Borne Disease - Alkhayat, Fatima Abdulla (2018)
A mosquito larval survey was conducted in Qatar from October 2013 to May 2015 to study the larval composition, distribution and larval habitats. Standard dipping technique was used to sample mosquito larvae from different breeding habitats, while aquatic insects were sampled using dipping and dragging techinques. Knowledge and awareness level among people of Qatar towards mosquitoes and mosquito-borne diseases were investigated between September and December 2013 through distributing a paper questionnaire. Six species representing three genera were recognized, namely, Anopheles stephensi, Culex pipiens, Culex quinquefasciatus, Culex mattinglyi. Ochlerotatus dorsalis and Ochlerotatus caspius.